Transglutaminase 2–mediated glutamine deamidation enhances p21 stability during senescence - Yi-Wen Liao; Hsi-Hsien Hsieh; Jin-Wei Yeh; Hsin-Chiao Wang; Shang-Yi Huang; Pei-Yu Wang; Jing-Jer Lin (Proceedings of the National Academy of Sciences, 2025)
The limited doubling capacity of human cells, known as replicative senescence or cellular senescence, is a major factor in cellular aging. This process is triggered by telomere erosion, which activates a p53-mediated DNA damage response (DDR) that halts cell proliferation. p53, a transcriptional regulator, responds to DNA damage by increasing the expression of the cyclin-dependent kinase inhibitor p21. p21 then arrests cells at specific stages of the cell cycle. Additionally, p53 upregulates serpinB2 (also known as plasminogen activator inhibitor-2, PAI-2), which stabilizes p21 in senescent cells. This study reveals that serpinB2 upregulation activates transglutaminase 2 (TGM2), which selectively deamidates multiple glutamine residues on p21, stabilizing the protein and halting cell proliferation in senescent cells. Moreover, inhibiting TGM2-mediated deamidation accelerates p21 degradation, delaying the onset of senescence. Notably, pharmacological inhibition of TGM2 improves aging phenotypes in an accelerated aging model of chronic kidney disease (CKD). These findings provide crucial insights into the role of TGM2-mediated enzymatic deamidation in senescence and its potential relevance to age-associated conditions.